Unions, monopolistic competition and unemployment - Rüdiger Wapler (Eberhard Karls Universität Tübingen, Wirtschaftswissenschaftliche Fakultät, 2000)
This paper develops a general equilibrium dual labour market model which incorporates union bargaining with monopolistically competitive firms. It is shown that not only the degree of union bargaining power but also the market power firms possess on the product market have a positive influence on unemployment. The reason for this is that less intense product market competition increases the negotiated wage rates as well as the price mark-up firms charge over their marginal costs, both of which reduce labour demand. It is also shown that higher competition intensity will force firms to merge to larger units.
urn:nbn:de:bsz:21-opus-19691
Keywords: J42; J51; J31; 330; Theorie der Arbeitslosigkeit; Arbeitsmarkttheorie; Mehr-Sektoren-Modell; Lohnverhandlungstheorie; Monopolistischer Wettbewerb; Mark-up Pricing; Theorie